(untitled) (Texas Journal of Engineering and Technology, 2023)
Wearable sensors and robotics are game-changers in the healthcare and assistive technology sectors in today’s age of fast technological breakthroughs. This research delves into the extensive benefits of these technologies, illuminating their present uses, astounding developments, and promising future. It examines the complicated problems that wearable sensors and robotics have to deal with and suggests solutions to help them advance. Researchers hope that by using these technological advancements, the future will be more accessible and empowering for those with impairments